Development of Latent Fingerprints on Thermal Paper by the Controlled Application of Heat. Issue 3 (29th March 2013) - Bond, John W.
Abstract Apparatus to produce a spatially and temporally uniform heat source is described and this is used to visualize latent fingerprints deposited onto thermal paper by raising the temperature of the paper. Results show an improvement over previous research when fingerprint deposits are aged or the developed fingerprints faint; visualization being enhanced by the use of a blue LED light source of 465 nm peak wavelength. An investigation of the components in fingerprint sweat likely to affect the solubility and hence color change of the dye present in the thermal paper has shown that polar protic solvents able to donate a proton are favored and a polar amino acid found commonly in eccrine fingerprint sweat (lysine) has been shown able to produce the desired color change. Aged fingerprint deposits on thermal paper from a variety of sources up to 4 years old have been visualized with this technique.